The structural behaviours of steel reinforced geopolymer concrete beams: An experimental and numerical investigation. (October 2021) - Pham, Dao Quang; Nguyen, Tuan Ngoc; Le, Son Tay; Pham, Tung Thanh; Ngo, Tuan Duc
Abstract: The environmental impact of traditional Ordinary Portland Cement (OPC) concrete is a significant problem that requires urgent solutions in the construction industry. The development of geopolymer concrete is one of the most significant breakthroughs in the process of replacing OPC concrete. Through comprehensive experimental and numerical analyses, this study investigates the structural behaviours of large-scale steel reinforced geopolymer concrete beams (GCBs) made from low-calcium fly ash and ground granulated blast furnace slag (GGBFS). Firstly, small-scale experiments were carried out to investigate the effects of water/binder and activator/binder ratios on the mechanical properties of geopolymer concrete (e.g. elastic modulus, compressive strength, direct tensile strength). The experimental results show that the mechanical properties of geopolymer concrete increases with increasing the activator/binder ratio and decreasing the water/binder ratio. Secondly, three groups of GCBs with different steel reinforcement ratios (D1-0.41%, D2-0.75%, and D3-1.5%) were made and four-point bending tests were conducted. The same mix proportion (water/binder of 0.45 and activator/binder of 0.08) with the compressive strength of 39.1 MPa, elastic modulus of 32.0 GPa, and the direct tensile strength of 3.06 MPa, was used for the three groups. The obtained moment–curvature results, which consists of three distinct stages (linear elastic, tension cracking of GCBs, and steel yielding), show that the three groups (D1-D3) behave in a ductile manner. Moreover, the moment capacity of GCBs increases when the steel reinforcement ratio increases (D1-21.5 kNm, D2-44.2 kNm and D3-83.6 kNm). Finally, nonlinear, three-dimensional finite element (FE) analysis based on the damage plasticity constitutive law was developed to capture and validate the structural behaviour of GCBs from the experiments. Numerical results indicate that the developed FE models accurately capture the structural behaviours (moment–curvature and cracking behaviour) of GCBs. The discrepancies between the numerical and experimental moment–curvature results are from 1 to 5% for the tensional cracking and yielding points. Therefore, the developed FE models can be used as an effective tool for the further development and design of geopolymer concrete structures.